Engaging Allene‐Derived Zwitterions in an Unprecedented Mode of Asymmetric [3+2]‐Annulation Reaction. Issue 33 (27th June 2016) - Sankar, Muthukumar G.; Garcia‐Castro, Miguel; Golz, Christopher; Strohmann, Carsten; Kumar, Kamal
Abstract: Catalytic addition of chiral phosphine, that is, ( R )‐ or ( S )‐SITCP, to an α‐substituted allene ester generated a zwitterionic dipole. Under optimized reaction conditions, this dipole could engage isatine‐derived N ‐Boc‐ketimines in a novel mode of [3+2] annulation reaction. Pyrrolinyl spirooxindoles are thus afforded in high yields and with excellent enantioselectivities. The unprecedented annulation reaction successfully facilitated the construction of sp 3 ‐rich and highly substituted 3, 2′‐pyrrolidinyl spirooxindoles supporting many chiral centers. Abstract : Taming a zwitterion : Chiral phosphine ( R )‐ or ( S )‐SITCP generates a zwitterion from α‐substituted allene ester that can engage the isatine derived ketimines in an unprecedented mode of [3+2] annulation reaction. This provides a facile asymmetric access to 3, 2′‐pyrrolidinyl spirooxindoles.